Regulatory Pathways That Facilitated Timely Registration of a New Group A Meningococcal Conjugate Vaccine for Africa's Meningitis Belt Countries - Dellepiane, Nora (Clin Infect Dis, 2015)
Background. Through its normative and public health leadership roles, the World Health Organization (WHO) plays a key role in the availability of vaccine products in low-and middle-income countries. The recent introduction of a new group A meningococcal conjugate vaccine, PsA-TT (MenAfriVac), in Africa exemplifies this process. WHO requires that any new vaccine to be introduced in countries for public health reasons and supplied through United Nations centralized mechanisms be licensed by the national regulatory agency (NRA) in the producing country, then prequalified and given a marketing authorization in the user countries. Methods. PsA-TT was manufactured by the Serum Institute of India, Ltd (SIIL), which submitted a license application in April 2009 to the Drug Controller General of India (DCGI), the Indian NRA responsible for licensing vaccines. WHO encouraged the DCGI to establish a collaboration with Health Canada's Centre for Vaccine Evaluation for the review. Through this collaborative effort, registration was facilitated and in December 2009 an export license was granted to SIIL, which subsequently submitted an application for WHO prequalification. Results. Given the importance of the vaccine, WHO “fast tracked” the prequalification review, and after a detailed review and site visit, WHO prequalification was granted to PsA-TT in June 2010. Country use of the new vaccine could not occur until the vaccine was a registered product in each country seeking its use. WHO facilitated country reviews by conducting regulatory training exercises (in French and English) for country NRA staff, which used the PsA-TT registration as a case study. Conclusions. PsA-TT was gradually registered in African countries as vaccine introduction proceeded. The regulatory pathway for this new group A meningococcal conjugate vaccine proved to be a useful training opportunity both in India and Africa, because the availability of the vaccine was a high African public health priority, as well as for WHO as a case study to facilitate registration of vaccines based on reliance on other regulatory bodies.